PATENT PROTECTIONS, CHALLENGES AND APPLICATIONS OF NANOTECHNOLOGY (Journal of Technology and Operations Management, 2020)
The primary focus of this paper is to highlight the importance of nanotechnology in terms of patents, challenges and applications. The nanotechnology has become a â€œkey value driverâ€ and significant role in the modern economy. The study contains an extensive review of existing literature related to patent issues, challenges and applications of nanotechnology. One of the challenges is when a nano-based product or process been recognized as a viable patented product. Chances for the patented nano-based product to be marketed is comparatively high as compared to non-patented product. It carries the weight as a high quality product, new, has better requirements, and can be very practical to be used. Patenting is a useful tool to protect its inventor, especially in an industry such as nanotechnology that is constantly producing new findings that eventually lead to the generation of commercialized products. Manufacturers of nano-based product often see the process of filing a patent is time consuming, yet once being granted, the effort would be very much worthy. It is timely to consider issues pertaining nanopatenting as a main feature among various parties involved for farecasting a better solution for the betterment of mankind. Authorities should grab opportunites related to nanotechnology and treat it as a new source of wealth combined with the protection provided by patent. Suggestions and recommendations are elaborated in details.